Sistem Reporting Surat Perintah Kerja Berbasis Website - Anggarini Puspita Rarasati; Deytizsa Putri Nur Azizah; Puput Arie Sugiyanto; Wasis Haryono (AMMA : Jurnal Pengabdian Masyarakat, 2025)
PT. Jomu Studio Indonesia is a manufacturing company engaged in the production of molding knives. The current management system for Work Orders (SPK) still relies on Microsoft Excel-based documentation, which leads to suboptimal data processing, reduced work efficiency, and an increased risk of recording errors. To address these challenges, a web-based SPK reporting system was developed. This study applies a software engineering approach using the Waterfall model of the Software Development Life Cycle (SDLC), consisting of analysis, design, implementation, testing, and maintenance stages. The results indicate that the web-based system successfully automates order input, SPK creation, progress monitoring, and real-time data reporting. The system is expected to assist the company in improving service quality and accelerating decision-making processes.